2021
DOI: 10.1016/j.carbpol.2020.117116
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic fermentation modifies the structures of pectic polysaccharides from carrot pulp

Abstract: Polysaccharides from fermented carrot pulp (WSP-p) show better anti-diabetic effects than those from un-fermented carrot pulp (WSP-n), and functional properties of polysaccharides depend on their structure. In this study, both WSP-p and WSP-n were separated into three homogeneous fractions as WSP-p-1, WSP-p-2, WSP-p-3, WSP-n-1, WSP-n-2 and WSP-n-3.The weight-average molecular weight of all of fractions from WSP-p showed a downward trend compared with the corresponding fraction from WSP-n. The functional groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…Bands in this region can be assigned to stretching vibrations of double bonds. The COO– doublet which is characteristic for pectic polysaccharides is located in this region ( Wan, Hong, Shi, Yin, Koev, Nie, et al, 2021 ). In addition, a water band appears at about 1635 cm −1 in this region and can shift depending on the strength of interactions.…”
Section: Principle and Spectrum Interpretationmentioning
confidence: 99%
“…Bands in this region can be assigned to stretching vibrations of double bonds. The COO– doublet which is characteristic for pectic polysaccharides is located in this region ( Wan, Hong, Shi, Yin, Koev, Nie, et al, 2021 ). In addition, a water band appears at about 1635 cm −1 in this region and can shift depending on the strength of interactions.…”
Section: Principle and Spectrum Interpretationmentioning
confidence: 99%
“…The hydrolyzate was diluted to be 20 μg/ml and analyzed by a high-performance anion-exchange chromatography with pulsed amperometric detection (Dionex ICS-5000, Thermo Fisher, Waltham, MA, United States). A CarboPac™ PA20 Guard Column (Ø3 mm × 30 mm, Thermo Fisher, Waltham, MA, United States) and CarboPac™ PA20 Analytical Column (Ø3 mm × 150 mm, Thermo Fisher, Waltham, MA, United States) were equipped in series and eluted with the mobile phase at 0.5 ml/min ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…After hydrolysis and acetylation, the partially methylated alditol acetates (PMAAs) were obtained. The PMAAs were analyzed by an Agilent 7890B/7000D GC-MS system (Agilent, Santa Clara, CA, United States) equipped with an SP-2330 column (Sigma-Aldrich, St. Louis, MO, United States) ( 23 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that there are some changes in plant polysaccharides before and after fermentation, which are demonstrated in the monosaccharide composition and biological activity. The changes were found to be related to the changes of carbohydrate active enzymes during fermentation. , In the carrot water-soluble polysaccharide, fermentation by probiotics led to enhanced immune regulation function and anti-diabetic effects. , The soybean soluble polysaccharide fermented by mixed bacteria was better able to promote the growth of microorganisms, and the monosaccharide composition, surface area, functional groups, and crystal structure therein were changed …”
Section: Introductionmentioning
confidence: 97%
“…9,10 In the carrot water-soluble polysaccharide, fermentation by probiotics led to enhanced immune regulation function and anti-diabetic effects. 11,12 The soybean soluble polysaccharide fermented by mixed bacteria was better able to promote the growth of microorganisms, and the monosaccharide composition, surface area, functional groups, and crystal structure therein were changed. 13 T h i s c o n t e n t i s Lanzhou lily (Lilium davidii var.…”
Section: Introductionmentioning
confidence: 99%